2015
DOI: 10.1055/s-0035-1548890
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Combined Resistance Training and Plyometrics on Physical Performance in Young Soccer Players

Abstract: This study aimed to determine the effects of combined resistance training and plyometrics on physical performance in under-15 soccer players. One team (n=20) followed a 6-week resistance training program combined with plyometrics plus a soccer training program (STG), whereas another team (n=18) followed only the soccer training (CG). Strength training consisted of full squats with low load (45-60% 1RM) and low-volume (2-3 sets and 4-8 repetitions per set) combined with jumps and sprints twice a week. Sprint ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
65
1
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(90 citation statements)
references
References 40 publications
5
65
1
6
Order By: Relevance
“…In another study, the best time of a repeated sprint ability test correlated low to moderately with BF, SJ, and P mean (Nikolaidis, Dellal, et al, 2015). Moreover, evidence for the relationship between sprint performance and muscle strength was provided by studies using a longitudinal design and observing similar changes in both parameters over time (De Hoyo et al, 2015;Franco-Márquez et al, 2015), too. For instance, a 6-week resistance training program combined with plyometrics plus a soccer training program induced gains for both 20 m performance and CMJ (Franco-Márquez et al, 2015).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In another study, the best time of a repeated sprint ability test correlated low to moderately with BF, SJ, and P mean (Nikolaidis, Dellal, et al, 2015). Moreover, evidence for the relationship between sprint performance and muscle strength was provided by studies using a longitudinal design and observing similar changes in both parameters over time (De Hoyo et al, 2015;Franco-Márquez et al, 2015), too. For instance, a 6-week resistance training program combined with plyometrics plus a soccer training program induced gains for both 20 m performance and CMJ (Franco-Márquez et al, 2015).…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, evidence for the relationship between sprint performance and muscle strength was provided by studies using a longitudinal design and observing similar changes in both parameters over time (De Hoyo et al, 2015;Franco-Márquez et al, 2015), too. For instance, a 6-week resistance training program combined with plyometrics plus a soccer training program induced gains for both 20 m performance and CMJ (Franco-Márquez et al, 2015). Faude et al (2013) identified that strength trained in combination with sprinting exercises resulted in greater adaptations in sprint speed as compared with strength training alone in high-level amateur soccer players.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Negra et al [22] found a significant increase in CMJ and SJ height after 8 (∆16 %, 16.6 %, respectively, both p < 0.01) and 12 weeks (both ∆23 %, both p < 0.01) of plyometric training in prepuberal male soccer players (12.7 ± 0.3 years). Franco-Marquez et al [8] studied the effects of 6 weeks of combined plyometric training and resistance training in post-puberal soccer players aged 15 years. Results from this study extended the previously presented findings and reported significant improvements in CMJ height (∆9 %, p < 0.001).…”
Section: Effects Of Spt Vs Upt On Measures Of Jumping Abilitymentioning
confidence: 99%
“…A linear velocity transducer (T-Force System, Ergotech, Murcia, Spain) was used to register MPV of the bar in each repetition. The following variables derived from this test were used for analysis: a) estimated one-repetition maximum (1RM est ) calculated from the MPV with the last load (kg) of the test as follows: 100 × LOAD / − 2.185 × MPV 2 − 61.53 × MPV + 122.5 (R 2 = 0.96, SEE = 5.5 % [33]); b) MPV attained against the first (F MPV ) and the last (L MPV ) absolute load common to pre-and post-tests [11].…”
Section: Isoinertial Progressive Loading Testmentioning
confidence: 99%
“…On the other hand, the effects of RT on physical performance rather than solely on strength gains should be of interest to coaches and to strength and conditioning professionals. A number of studies report a large to very large relationship between lower-body strength measured through the back squat exercise, and sprint and jump performance, suggesting that increasing lower-body strength is fundamental when attempting to improve performance in these motor skills [8,11,45]. Despite the influence of training load on changes induced by RT, few studies have analyzed the effect of different loading magnitudes on changes in sprint ability and jump height [15,25,44].…”
mentioning
confidence: 99%